Archives in Appalachia : A Directory - Garrison, Ellen (Appalachian State University, 1985)
Archives in Appalachia: A Directory consists of entries describing 181 repositories in 195 counties in the South-Central Appalachia region which hold historical records documenting the political, social, cultural, and economic history of the region, and a list of (3z(BComing Attractions,(3y (Bagencies which did not collect manuscript material but which planned to do so in the future. Also included in this directory are indexes sorted by type of material and by subject matter which enable researchers to locate selected genres of material.s
English
Keywords: Regional studies; Social Science; Regional Studies